2020
DOI: 10.1002/aelm.202000571
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkled‐Surface‐Induced Memristive Behavior of MoS2 Wrapped GaN Nanowires

Abstract: Figure 6. a) HR-TEM images of MoS 2-GaN NWs. b) Schematic diagram of the migration of O ions in the interlayered structure of MoS 2. Schematic diagrams of the memristive model during c) initial, d) SET, and e) RESET process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The template was applied to the circular top electrode with a diameter of 1 mm. A similar fabrication process was described in our previous paper and the GP formed the bottom electrode in the photoelectronic test.…”
Section: Methods and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The template was applied to the circular top electrode with a diameter of 1 mm. A similar fabrication process was described in our previous paper and the GP formed the bottom electrode in the photoelectronic test.…”
Section: Methods and Characterizationmentioning
confidence: 99%
“…By taking advantage of the large surface-to-volume ratio of one-dimensional (1D) materials and defect states galore, a functionalized and decorated surface can enhance the PPC effect, especially the controllable SDP. III–V nanowire arrays (NWAs), in particular GaN, are widely used in flexible optoelectronic devices and have great potential in flexible OESDs due to the high alignment, photoelectronic sensitivity, carrier migration rate, and adjustable band gap. The PPC effect in the GaN-based nanostructures has been studied. For example, Chen et al have studied the size-dependent PPC effect in a single GaN NW and found that the decay time is relative to surface band bending ascribed to oxygen or surface polarity . The nanoporous GaN arrays have also been shown to enhance the PPC effect more than bulk GaN .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Huang et al described a novel memory device based on wrinkled MoS 2 -GaN nanowires (NWs), showing good stability and retention characteristics of 798 cycles and 3.4 × 10 3 s with a low switching voltage [147]. Defects may be formed in the wrinkled structure, causing O ions to migrate along the wrinkled surface of NWs, and resulting in the memristive behavior of the device.…”
Section: Other Applicationsmentioning
confidence: 99%
“…As for GaN-WS2, a combination of these materials shows promise in optoelectronics [38] and photocatalysis [25], since WS2 can also be an efficient catalyst [39]. Regarding 1D-1D core-shell nanostructures, growth of MoS2-wrapped GaN NWs has recently been demonstrated by Ji et al via direct deposition of MoS2 on GaN NWs with magnetron sputtering [40] and GaN-MoSx coreshell NWs by Zhou et al via electrodeposition [41]. The few previous studies clearly demonstrate the potential of such heterostructures; however, the development of other versatile fabrication methods is still needed for further progress.…”
Section: Introductionmentioning
confidence: 99%